2020
DOI: 10.20517/2347-8659.2020.22
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of inflammation and repair after ischemic brain injury

Abstract: After ischemic stroke, proinflammatory molecules known as danger-associated molecular patterns (DAMPs) originating from damaged brain cells recruit and activate immune cells (neutrophils, macrophages, lymphocytes) further eliciting innate and adaptive immunity. During the acute phase from day 1 to day 3 of the stroke onset, macrophages play a major role in the progression of inflammation, promoting the destruction of brain tissue. During the recovery phase, from day 3~4 to day 7 after stroke onset, infiltratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 109 publications
0
3
0
Order By: Relevance
“…Among the leukocytes infiltrating the brain are blood-derived monocytes/macrophages, which infiltrate the cerebral tissue in the hyperacute stage of stroke (<24 h) [ 100 ]. They have similar functions to resident microglia and are very difficult to differentiate from the latter [ 43 ], with researchers using chimera mice with enhanced colored fluorescent protein bone marrow for this aim [ 101 ].…”
Section: Inflammation In Ischemia/reperfusion Injuriesmentioning
confidence: 99%
“…Among the leukocytes infiltrating the brain are blood-derived monocytes/macrophages, which infiltrate the cerebral tissue in the hyperacute stage of stroke (<24 h) [ 100 ]. They have similar functions to resident microglia and are very difficult to differentiate from the latter [ 43 ], with researchers using chimera mice with enhanced colored fluorescent protein bone marrow for this aim [ 101 ].…”
Section: Inflammation In Ischemia/reperfusion Injuriesmentioning
confidence: 99%
“…It is reported that macrophages are activated in the early stages of inflammation after stroke (around 24 h after stroke onset) which leads to the secretion of inflammatory cytokines that exacerbate brain damage [ 64 ]. Our results show that HR EVs protect macrophages from LPS-induced inflammation and we, therefore, examined whether C2C12 EVs can enter the ischemic brain after systemic injection.…”
Section: Resultsmentioning
confidence: 99%
“…However, some important differences exist. The postsurgical state may extend beyond immediate recovery and the postoperative period, lasting months or representing a new allesotatic state [28,[37][38][39][40]. Consequently, an individual cannot regain preoperative health or homeostasis.…”
Section: New Paradigm Of Anesthesia Carementioning
confidence: 99%